Assessment of Aspergillus spp. in a Modern Broiler Breeder Structure. (February 2015) - Moreira, F. A.; Cardoso, L.; Coelho, A. C.
Members of the genus Aspergillus are ubiquitous opportunistic saprophytic fungi regarded as major respiratory pathogens in birds, which can cause significant economic losses in chickens, with mortality, decreased weight gain and slaughter condemnations. Initial contamination of broiler poultry farms often occurs through use of contaminated litter or introduction of day-old birds that have received Aspergillus spp. conidia from hatchery facilities. This study evaluated different conditions at the broiler breeder level and tried to ascertain different risk factors connected to this contamination that can thrive in the hatchery. In most modern broiler breeder reproduction farms in Portugal, birds are kept on the ground and eggs are collected by means of an egg belt system. A total of 210 samples were collected from 30 flocks (one sample per variable and per flock). In each flock, the following samples were taken: 30 samples from egg surfaces (10 cm 2 ) of randomly collected eggs from the floor (dirty eggs); 30 samples from eggs from the egg belt system (clean eggs); 30 samples from the egg belt system (10 cm 2 of the egg belt surface) (egg belt system). Samples were tested using a swab soaked in distilled water and seeded on Rose Bengal (RB) medium for initial cultivation. The other sample from the egg belt system was performed putting the open RB plate on the running egg belt system for 5 min. Aspergillus spp. were detected in 46.2% of the samples (97/210), namely in 50% of clean eggs and 40% of dirty eggs. In the egg belt system, 56.7% of the samples were positive. Regarding feed and litter samples, 43.3% and 33.3% accordingly were positive. Samples directly collected from birds were 23.3% positive. Specific broiler breeder conditions, feed stuffs and animals are potential sources of fungi contamination in hatcheries and to the chick quality in broiler farms.